Successful Non-Surgical Intervention for Massive Gastric Distention due to Malignant Duodenal Obstruction - Yazeed A. Khojah (Journal of King Abdulaziz University: Medical Sciences, 2023)
Gastroduodenal obstruction in pancreatic cancer is common and sometimes challenging to treat. A 35-year-old man with advanced pancreatic cancer receiving palliative chemotherapy presented with worsening abdominal pain, nausea, vomiting and increased abdominal girth. Computed tomography scan of the abdomen revealed signifi cant malignant duodenal obstruction with massive gastric distention. A non-surgical endoscopic intervention with placement of a self-expanding metallic duodenal stent successfully relieved the obstruction and ameliorated symptoms. The patient was able to resume eating normally again. Gastrointestinal stenting is a less invasive and eff ective alternative to surgical gastrojejunostomy. Stent placement as a palliative treatment for patients with malignant duodenal obstruction and massive gastric distention may be considered as a first line treatment for such patients.